2010
DOI: 10.1002/app.32035
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of electrospun eggshell membrane nanofibers by treatment with catechin

Abstract: Optimum processing conditions for the electrospinning of water-soluble eggshell membrane (S-ESM) were investigated. Two biocompatible polymers, poly(ethylene oxide) (PEO) and poly(vinyl alcohol) (PVA), were used to improve the processability of S-ESM for electrospinning in aqueous media. Uniform nanofibers with average diameters of 240 and 335 nm were successfully electrospun for blend ratios at S-ESM/PEO ¼ 95 : 5 and S-ESM/PVA ¼ 60 : 40 with a solutes concentration of 20 and 18 wt %, respectively. Insoluble S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Blendelectrospinning method is used in the study to improve the electrospinnability and mechanical properties of SEP. Yi et al [21] has prepared the poly (ethylene oxide) (PEO)/SEP nanofibers by electrospinning successfully, while the nanofibers need to be treated by cross-linking agent due to the quick and complete dissolution in the water. The similar phenomenon was observed in another study, and the fibers were treated by catechin to improve the water insolubility [22]. While in these studies, the toxicity of crosslinking agents still remains a concern.…”
Section: Introductionsupporting
confidence: 79%
“…Blendelectrospinning method is used in the study to improve the electrospinnability and mechanical properties of SEP. Yi et al [21] has prepared the poly (ethylene oxide) (PEO)/SEP nanofibers by electrospinning successfully, while the nanofibers need to be treated by cross-linking agent due to the quick and complete dissolution in the water. The similar phenomenon was observed in another study, and the fibers were treated by catechin to improve the water insolubility [22]. While in these studies, the toxicity of crosslinking agents still remains a concern.…”
Section: Introductionsupporting
confidence: 79%
“…Polyethylene oxide (PEO) is one kind of water-soluble polymer which had been utilized as a carrier polymer and has been shown to have a number of advantages for electrospinning, these include low toxicity allowing for its potential use as a food additive, and of course inherent electrospinning ability in its own right. PEO has been used as a carrier polymer in a biopolymer solution with silk 26 , soy protein 27 , eggshell protein 28 and whey protein isolate 29 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the further application of ESM is limited by its insolubility, therefore, rather than employing natural ESM, water-soluble ESM (S-ESM) from natural hen ESM has been considered to produce the regenerated ESM nanofibers. Recently, several studies reported that S-ESM fibers can be successfully fabricated by blending supporting polymers PEO and PVA [10,11], because S-ESM itself can not be electrospun due to the low molecular weight resulting in insufficient viscosity for spinning. Further improvement in this type of processing is necessary for electrospinning of S-ESM/PVA blends in aqueous media.…”
Section: Introductionmentioning
confidence: 99%